2013
DOI: 10.1111/bjhp.12071
|View full text |Cite
|
Sign up to set email alerts
|

Effective behaviour change techniques in smoking cessation interventions for people with chronic obstructive pulmonary disease: A meta‐analysis

Abstract: PurposeThe purpose of this study was to identify the behaviour change techniques (BCTs) that are associated with greater effectiveness in smoking cessation interventions for people with chronic obstructive pulmonary disease (COPD).MethodsA systematic review and meta-analysis was conducted. Web of Knowledge, CINAHL, EMBASE, PsycINFO, and MEDLINE were searched from the earliest date available to December 2012. Data were extracted and weighted average effect sizes calculated; BCTs used were coded according to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 78 publications
3
65
0
2
Order By: Relevance
“…Several reviews have noted the benefits of BCTs aligned with control theory such as self‐monitoring (e.g., Bartlett et al ., ; Olander et al ., ), and Michie et al . () noted that interventions comprising more BCTs from control theory were more effective than those interventions that used less.…”
Section: Discussionmentioning
confidence: 90%
“…Several reviews have noted the benefits of BCTs aligned with control theory such as self‐monitoring (e.g., Bartlett et al ., ; Olander et al ., ), and Michie et al . () noted that interventions comprising more BCTs from control theory were more effective than those interventions that used less.…”
Section: Discussionmentioning
confidence: 90%
“…This is especially important regarding the patients’ inactive lifestyle, as proxies can positively affect this. In fact, behavioural change is effective when social support (such as proxies’ support) is included . Shared insight in problematic ADLs is, therefore, necessary and an important step in behavioural change.…”
Section: Discussionmentioning
confidence: 99%
“…By selfmonitoring, patients can keep check on their chronic condition and experience the effect of their behaviour on clinical outcomes. 13,23,24 Self-monitoring can also increase selfefficacy for health-related behaviour. 25 This trial, which had a heterogeneous study population, showed a significant effect on self-monitoring.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%